2020
DOI: 10.1111/ecc.13330
|View full text |Cite
|
Sign up to set email alerts
|

The significance of the Interpersonal‐Psychological Theory of Suicide in an oncological context—A scoping review

Abstract: Objectives Since individuals afflicted with cancer are at an elevated risk of dying by suicide, understanding suicide‐related ideation and behaviours is critical in identifying vulnerable patients. The interpersonal theory of suicide (IPTS) provides a framework to research risk factors for suicide and has been validated in different samples. The aim of this scoping review is to study literature related to IPTS and cancer patients. Methods This scoping review was registered with the OPEN Science Framework (osf.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 65 publications
(161 reference statements)
0
3
0
Order By: Relevance
“…The physical condition caused by MS makes patients helpless, and they may need help from others to cope with the disease, so they feel like a burden. Findings from a variety of studies have shown that both thwarted belongingness and perceived burdensomeness are related to suicidal ideation in patients with chronic diseases Campos et al, (2018), cancer Schomberg et al, (2021), and student populations (Kiani et al, 2019).…”
Section: Medical Sciencementioning
confidence: 99%
“…The physical condition caused by MS makes patients helpless, and they may need help from others to cope with the disease, so they feel like a burden. Findings from a variety of studies have shown that both thwarted belongingness and perceived burdensomeness are related to suicidal ideation in patients with chronic diseases Campos et al, (2018), cancer Schomberg et al, (2021), and student populations (Kiani et al, 2019).…”
Section: Medical Sciencementioning
confidence: 99%
“… 8 A cancer diagnosis may represent a life event that triggers both interpersonal struggles, offers little hope for change in the future, and increases a patient's capability for suicide through an increase in pain tolerance and acceptance of death. 8 Cancer diagnosis and subsequent treatment may diminish social engagement, reciprocal relationships, and perceived belonging, while the physical and financial strain of cancer may increase feelings of burdensomeness. Among cancer patients, physical stressors associated with suicidal behavior include pain, disfigurement, body‐image concerns, and dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…7 The Interpersonal Theory of Suicide posits that active suicidal desire is driven by the presence of thwarted belongingness, perceived burdensomeness, and hopelessness that these interpersonal struggles will improve, while the capacity for suicidal behavior is an independent process driven by fearlessness and familiarity with pain. 8 A cancer diagnosis may represent a life event that triggers both interpersonal struggles, offers little hope for change in the future, and increases a patient's capability for suicide through an increase in pain tolerance and acceptance of death. 8 Cancer diagnosis and subsequent treatment may diminish social engagement, reciprocal relationships, and perceived belonging, while the physical and financial strain of cancer may increase feelings of burdensomeness.…”
Section: Introductionmentioning
confidence: 99%